THE IMPORTANCE OF ENGLISH IN GLOBAL COMMUNICATION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In this article, I will explain the multifaceted role of English as a public language, the complex dynamics related to its historical development and widespread use will be reflected.  This article highlights the benefits of English in facilitating international communication, collaboration and knowledge sharing, while highlighting the challenges of cultural appropriation and marginalization of other languages.   Through this language, we can understand people of different cultures in a comprehensive way and it plays a key role in bringing globalization to us.